The Poverty of Growth with Interdependent Utility Functions - Peter Salamon; John Komlos (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
We argue that with interdependent utility functions growth can lead to a decline in total welfare of a society if the gains from growth are sufficiently unequally distributed in the presence of negative externalities, i.e., envy.
urn:nbn:de:bvb:19-epub-619-4
Keywords: D62; D63; D64; O00; 330; Interdependent utility functions; growth; inequality